2013
DOI: 10.5489/cuaj.245
|View full text |Cite
|
Sign up to set email alerts
|

Can 3T multiparametric magnetic resonance imaging accurately detect prostate cancer extracapsular extension?

Abstract: Background: Accurate staging is essential to determine the correct management of patients diagnosed with prostate cancer. We assess the accuracy of 3T multiparametric magnetic resonance imaging (MRI) with endorectal coil (3TemMRI) in detecting prostate cancer local extension. Methods: We retrospectively reviewed charts from January 2008 to July 2012 from all patients undergoing radical prostatectomy. Patients were only included if 3TemMRI and radical prostatectomy were performed at our institution. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…[4,5,[9][10][11] In our study, the specificity, sensitivity, and positive and negative predictive values of ECE were 95%, 25%, 66%, and 77%, respectively. We evaluated the patients who had RARP with or without preoperative MRIguided dissection planning.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[4,5,[9][10][11] In our study, the specificity, sensitivity, and positive and negative predictive values of ECE were 95%, 25%, 66%, and 77%, respectively. We evaluated the patients who had RARP with or without preoperative MRIguided dissection planning.…”
Section: Discussionmentioning
confidence: 87%
“…[5][6][7][8][9] It is estimated that mp-MRI detects ECE with 48-76% accuracy. [4,[10][11][12][13][14] Walz et al [15] detailed the anatomy of the prostate and adjacent tissues, especially the fascia and NVB. In light of these studies, preoperative mp-MRI of the prostate may guide surgeons' dissection plans for RARP.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of pre-treatment local staging by MRI ± DWI, DCE, MRS on clinical and patient outcomes is still not clear. Although studies consistently demonstrated upstaging by imaging compared to clinical staging, this was only correct by pathology in a few studies and the magnitude was highly variable (11% to 85%), 16,17,32,34,38,41,44 thus making any conclusions to be drawn imprecise. There was limited information on the outcome of risk stratification category; 30,34 however, the results were consistent with the trend of upstaging.…”
Section: Discussionmentioning
confidence: 99%
“…There were 20/21 (95.2%) studies that consistently demonstrated upstaging by MRI, 33,36 and upstaging by MRI compared to routine clinical staging. 12,13,16,17,20,21,23,30,32,34,[37][38][39][40][41][42][43][44][45] Upstaging by MRI was correct by pathology in seven studies, with a range from 11-85%. 16 …”
Section: Key Evidencementioning
confidence: 99%
See 1 more Smart Citation